Surface-treated steel sheet

JP7939577B2Active Publication Date: 2026-10-22NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024574999
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-01
Filing Date
2024-02-01
Publication Date
2026-10-22
Estimated Expiration
2044-02-01

AI Technical Summary

Benefits of technology

【0009】 以上説明したように本発明によれば、合金化溶融亜鉛めっき鋼板を素材とした表面処理鋼板において、表面処理皮膜の密着性を担保しつつ、耐食性の担保と光沢感の向上とを両立することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939577000003
    Figure 0007939577000003
  • Figure 0007939577000004
    Figure 0007939577000004
  • Figure 0007939577000005
    Figure 0007939577000005
Patent Text Reader

Abstract

[Problem] To provide a surface-treated steel sheet in which the adhesion of a surface-treating film can be ensured, and both of the ensuring of corrosion resistance and the improvement in glossiness can be achieved. [Solution] A surface-treated steel sheet according to the present invention comprises: a galvannealed steel sheet including a steel sheet that serves as a base material and a galvannealed layer that is provided on the steel sheet; and a surface-treating layer provided on the galvannealed steel sheet. The surface-treating layer contains a base resin and SiO2-coated Al flakes that are Al flakes of which the surfaces are coated by a SiO2 layer. The average thickness of the SiO2 layer is 10-100 nm. The average particle size R of the SiO2-coated Al flakes is 1.00-30.00 μm. The ratio (R / t) of the average particle size to the average thickness t of the SiO2-coated Al flakes is 10 or greater. The ratio of coverage of the surface of the galvannealed steel sheet by the SiO2-coated Al flakes is 20% or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-treated steel sheet.

Background Art

[0002] Zinc-based plated steel sheets are materials widely used in fields such as architecture and automobiles from the viewpoint of improving the corrosion resistance of structural members (for example, refer to Patent Document 1 and Patent Document 2 below). The zinc-based plated steel sheet as a material is processed into various shapes, and then, if necessary, joined to each other by fastening members such as screws and bolts, or by joining treatment using various welding methods, to obtain a desired structural member having a shape.

[0003] Here, in order to improve the corrosion resistance of the manufactured structural member, various surface treatment films may be formed on the surface of the zinc-based plated steel sheet that is the material. In addition, in order to improve the design properties of the manufactured structural member, various colored films may be formed on the surface of the zinc-based plated steel sheet that is the material. In order to improve the adhesion of these films during processing when manufacturing structural members, an alloyed hot-dip zinc-coated steel sheet (Galva-Annealed Steel sheet: GA) having an uneven plating surface may be used as the material.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of Invention

Problems to be Solved by the Invention

[0005] Here, when a surface treatment film is formed on the surface of an alloyed hot-dip galvanized steel sheet to ensure corrosion resistance, since the alloyed hot-dip galvanized steel sheet is a galvanized steel sheet with low glossiness, the galvanized steel sheet with low glossiness is further covered with the surface treatment film, so that the desired glossiness cannot be obtained. For this reason, it may not be possible to achieve both the guarantee of corrosion resistance and the improvement of glossiness, and depending on the application of the structural member to be manufactured, it may be difficult to use the alloyed hot-dip galvanized steel sheet as the original sheet.

[0006] Accordingly, the present invention has been made in view of the above problems, and an object of the present invention is to provide a surface-treated steel sheet that uses an alloyed hot-dip galvanized steel sheet as a base material, and is capable of achieving both the guarantee of corrosion resistance and the improvement of glossiness while ensuring the adhesion of the surface treatment film. [Means for Solving the Problems]

[0007] In order to solve the above problems, as a result of intensive studies by the present inventors, the present inventors have found that it is possible to achieve both the guarantee of corrosion resistance and the improvement of glossiness by incorporating a glossy substance into the surface treatment layer formed on the alloyed hot-dip galvanized layer. However, it has also been found that simply incorporating a glossy substance causes the glossy substance to aggregate in the surface treatment layer, making it impossible to obtain the desired effect. Accordingly, the present inventors have conducted further studies based on these findings, and as a result, have arrived at the present invention as described below. The gist of the present invention completed based on such findings is as follows.

[0008] (1) A surface-treated steel sheet comprising: (1) a base material steel sheet and an alloyed hot-dip galvanized layer on the steel sheet; and a surface treatment layer on the alloyed hot-dip galvanized layer, wherein the surface treatment layer contains a base resin and SiO2-coated Al flakes, which are Al flakes whose surface is covered with an SiO2 layer; the average thickness of the SiO2 layer is 10 to 100 nm; the average particle size R of the SiO2-coated Al flakes is 1.00 to 30.00 μm; the ratio of the average particle size to the average thickness t of the SiO2-coated Al flakes (R / t) is 10 or more; and the coverage rate of the surface of the alloyed hot-dip galvanized steel sheet by the SiO2-coated Al flakes is 20% or more. Here, the coverage ratio is the value given by the following formula (1) when the surface treatment layer, the alloyed hot-dip galvanized layer, and the cross-section obtained by cutting the steel plate in the thickness direction are observed with a scanning electron microscope, and the size of the observation field in the direction perpendicular to the thickness direction is denoted as L0, and the length of the SiO2-coated Al flakes present in the observation field is denoted as ΣLn. Coverage rate [%] = (ΣLn / L0) × 100 ... Equation (1) (2) The Al content in the surface treatment layer is 0.15 to 12.00 g / m 2 The surface-treated steel sheet described in (1). (3) The surface-treated steel sheet according to (1) or (2), wherein the surface roughness of the alloyed hot-dip galvanized layer is 1.0 to 10.0 μm. (4) The surface-treated steel sheet according to any one of (1) to (3), wherein the average thickness of the surface-treated layer is 1.0 to 10.0 μm. (5) The surface-treated steel sheet according to any one of (1) to (4), wherein the average particle size R of the SiO2-coated Al flakes is 10.00 to 30.00 μm. (6) The SiO2-coated Al flake is viewed in plan from above in the thickness direction of the SiO2-coated Al flake, and the minor axis of the SiO2-coated Al flake is R S , the major axis is R L When written as such, the ratio (R L / R S) is a surface-treated steel sheet described in any one of (1) to (5), with a value of 1.0 to 5.0. (7) A surface-treated steel sheet according to any one of (1) to (6), wherein the coverage ratio is 50% or more. [Effects of the Invention]

[0009] As described above, according to the present invention, in a surface-treated steel sheet made from alloyed hot-dip galvanized steel sheet, it is possible to ensure the adhesion of the surface treatment film while simultaneously ensuring corrosion resistance and improving gloss. [Brief explanation of the drawing]

[0010] [Figure 1] This is a schematic explanatory diagram showing an example of the configuration of a surface-treated steel sheet according to an embodiment of the present invention. [Figure 2] This is a schematic diagram illustrating the SiO2-coated Al flakes present in the surface-treated steel sheet according to the same embodiment. [Figure 3] This is a schematic diagram illustrating the distribution state of SiO2-coated Al flakes in the surface treatment layer of the surface-treated steel sheet according to the same embodiment. [Figure 4] This is a schematic diagram illustrating the coverage ratio of the surface-treated steel sheet according to the same embodiment. [Modes for carrying out the invention]

[0011] Preferred embodiments of the present invention will be described in detail below with reference to the attached drawings. In this specification and drawings, components having substantially the same functional configuration are denoted by the same reference numerals, and redundant descriptions will be omitted.

[0012] (Regarding surface-treated steel sheets) The overall structure of the surface-treated steel sheet according to an embodiment of the present invention will be described below with reference to Figure 1. Figure 1 is a schematic explanatory diagram showing an example of the configuration of the surface-treated steel sheet according to this embodiment.

[0013] The surface-treated steel sheet according to this embodiment is particularly suitable as a material for structural members manufactured by joining together a plurality of parts processed into a desired shape.

[0014] As schematically shown in Figure 1, the surface-treated steel sheet 1 according to this embodiment comprises a base steel sheet 10, an alloyed hot-dip galvanized layer 20 located on both surfaces of the base steel sheet 10, and a surface treatment layer 30 located on the surface of the alloyed hot-dip galvanized layer 20.

[0015] In the following explanation, we will use the case shown in Figure 1, where the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 are formed on both surfaces of the base steel sheet 10, as an example.

[0016] <Regarding the base steel plate 10> The dimensions, composition, structure, and mechanical properties of the base steel sheet 10 used as the base material for the surface-treated steel sheet 1 according to this embodiment are not particularly limited. For example, various types of steel sheets can be used as the base steel sheet 10 depending on the mechanical strength (e.g., tensile strength) required for the surface-treated steel sheet 1. Examples of such base steel sheets 10 include steel materials standardized by Japanese Industrial Standards (JIS), such as carbon steel, alloy steel, and high-tensile steel used for general structural and machine structural purposes. Specific examples of such steel materials include cold-rolled steel, hot-rolled steel, hot-rolled steel sheets for automobile structures, hot-rolled high-tensile steel sheets for automobile processing, cold-rolled steel sheets for automobile structures, cold-rolled high-tensile steel sheets for automobile processing, and high-tensile steel generally called hot-stamped steel that has been quenched during hot working. The composition of such steel materials is not particularly limited, but in addition to Fe and C, it may contain one or more of the following: Si, Mn, S, P, Al, N, Cr, Mo, Ni, Cu, Ca, Mg, Ce, Hf, La, Zr, and Sb. One or more of these optional additive elements can be appropriately selected to obtain the desired material strength and formability, and their content can also be adjusted as appropriate.

[0017] Among the high-strength steels described above, using high-strength steel with a tensile strength of 780 MPa or higher (so-called 780 MPa class or higher high-strength steel) is preferable because it can further improve the robustness of the manufactured articles. Here, the tensile strength of the base steel plate 10 can be measured by a known method. For example, a test piece can be prepared from a part of the steel plate whose tensile strength is to be measured, as specified in JIS Z 2241:2011, and the tensile strength of the obtained test piece can be measured using the specified method.

[0018] Furthermore, the thickness of the base steel sheet 10 is not particularly limited and can be set appropriately according to the mechanical strength and other requirements for the surface-treated steel sheet 1.

[0019] <About the alloyed hot-dip galvanized layer 20> The alloyed hot-dip galvanized layer 20 (hereinafter sometimes simply referred to as "plating layer 20") according to this embodiment is formed on both surfaces of the base steel sheet 10 as described above. As mentioned earlier, since the surface of the alloyed hot-dip galvanized layer 20 has irregularities, it is possible to ensure adhesion between the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 formed on the alloyed hot-dip galvanized layer 20 through a so-called anchoring effect.

[0020] The surface roughness of the alloyed hot-dip galvanized layer 20 according to this embodiment is preferably 1.0 to 10.0 μm, as defined by the arithmetic mean roughness Ra in JIS B 0601:2001. The presence of irregularities on the surface of the alloyed hot-dip galvanized layer 20, such that the surface roughness is within the range of 1.0 to 10.0 μm, allows the SiO2-coated Al flakes, described later, to be retained in the surface depressions. This makes it possible to achieve the coating rate and gloss described in detail below while suppressing the SiO2-coated Al flake content. The surface roughness of the alloyed hot-dip galvanized layer 20 is more preferably 1.2 μm or more. Furthermore, the surface roughness of the alloyed hot-dip galvanized layer 20 is more preferably 5.0 μm or less.

[0021] The amount of the alloyed hot-dip galvanized layer 20 can be measured, for example, as follows: Cut a sample of 30 mm x 30 mm in size in plan view from the surface-treated steel sheet 1 of interest. Remove the surface treatment layer 30 described later from the cut sample using a coating remover or the like to expose the alloyed hot-dip galvanized layer 20. Then, measure any number of locations (for example, 3 locations) on the sample after the surface treatment layer 30 has been removed using a surface roughness meter compliant with JIS B 0601:2001 (for example, SURFCOM manufactured by Tokyo Seimitsu Co., Ltd.). The average of the obtained multiple measurement values ​​by the number of measurement locations can be used as the surface roughness of the alloyed hot-dip galvanized layer 20.

[0022] The method for forming the alloyed hot-dip galvanized layer 20 is not particularly limited, and it can be formed using various known plating baths and alloying methods.

[0023] There is no specific requirement for the amount of the alloyed hot-dip galvanized layer 20 to be applied, but for example, 15 to 120 g / m² per side of the base steel sheet 10. 2 It is preferable that the amount of alloyed hot-dip galvanized layer 20 adheres to the above-mentioned range, thereby enabling the surface-treated steel sheet 1 according to this embodiment to exhibit sufficient corrosion resistance.

[0024] The amount of the alloyed hot-dip galvanized layer 20 can be measured, for example, as follows: A sample measuring 30 mm x 30 mm in plan view is cut from the surface-treated steel sheet 1 of interest. When cutting the sample, the entire thickness direction should be cut out. The surface treatment layer 30, described later, is removed from the cut sample using a coating remover or the like. The mass of the sample after the surface treatment layer 30 has been removed is measured in advance. A tape seal is applied to one side of the sample to prevent the alloyed hot-dip galvanized layer 20 on that side from dissolving in the next step. The sample is then immersed in a 10% HCl aqueous solution with an inhibitor added to pickle and remove the alloyed hot-dip galvanized layer 20, and the mass of the sample after pickling is measured. From the change in mass of the sample before and after pickling, the amount of the alloyed hot-dip galvanized layer 20 attached to each side can be determined.

[0025] As described above, the surface-treated steel sheet 1 according to this embodiment can be said to be an alloyed hot-dip galvanized steel sheet having a base steel sheet 10 and an alloyed hot-dip galvanized layer 20 as the base material when the surface treatment layer 30 described below is formed.

[0026] <About the surface treatment layer 30> The surface treatment layer 30 according to this embodiment is formed on the surface of the alloyed hot-dip galvanized layer 20 as described above. As schematically shown in Figure 1, the surface treatment layer 30 contains a base resin 301 and SiO2-coated Al flakes 303.

[0027] [About base resin 301] The base resin 301 not only functions as a binder resin in the surface treatment layer 30, but also contributes to the corrosion resistance of the surface-treated steel sheet 1 according to this embodiment. In the surface treatment layer 30 according to this embodiment, various known organic resins such as polyester resins, polyurethane resins, and acrylic resins can be used as the base resin 301. These organic resins may be used individually or in combination of two or more. In addition to the above organic resins, the base resin 301 may also contain various inorganic compounds such as zirconium ammonium carbonate and silane coupling agents as additives.

[0028] Here, the content of the base resin 301 in the surface treatment layer 30 is preferably, for example, 40% by mass or more relative to the film solid content. By setting the content of the base resin 301 to 40% by mass or more, the corrosion resistance of the surface treatment layer 30 can be improved. Furthermore, the content of the base resin 301 in the surface treatment layer 30 is preferably, for example, 90% by mass or less, and more preferably 70% by mass or less, relative to the film solid content. By setting the content of the base resin 301 to 90% by mass or less, the corrosion resistance of the surface treatment layer 30 can be improved while ensuring the performance required of a film other than corrosion resistance.

[0029] [About SiO2-coated Al flake 303] SiO2-coated Al flakes 303 (hereinafter sometimes simply referred to as "Al flakes 303") are glossy materials in which the surface of a thin, flake-like substance made of Al is coated with an SiO2 layer, and are contained in the surface treatment layer 30 according to this embodiment. By containing SiO2-coated Al flakes 303 in the surface treatment layer 30, it is possible to improve the glossiness of the surface-treated steel sheet 1 according to this embodiment. Furthermore, because the surface of the Al flakes is coated with an SiO2 layer, aggregation of the Al flakes in the surface treatment layer 30 can be prevented, and the SiO2-coated Al flakes 303 can be appropriately dispersed in the surface treatment layer 30. As a result, it is possible to obtain higher glossiness. Consequently, the surface-treated steel sheet 1 according to this embodiment can achieve both guaranteed corrosion resistance and improved glossiness.

[0030] In this embodiment, the surface treatment layer 30 is formed by applying and drying a surface treatment agent containing at least a base resin 301 and SiO2-coated Al flakes 303. If the SiO2 layer is not present on the surface of the Al flakes, the Al flakes may react with any moisture present in the surface treatment agent to generate hydrogen, potentially preventing the effective utilization of the Al flakes contained in the surface treatment agent in terms of coating the alloyed hot-dip galvanized layer 20. Therefore, by coating the surface of the Al flakes with an SiO2 layer, the reaction between the Al and any moisture present in the surface treatment agent can be suppressed, making it possible to effectively utilize the Al flakes. This suppression of the reaction between moisture and Al can be achieved by setting the average thickness of the SiO2 layer to 10 nm or more. From this viewpoint, the average thickness of the SiO2 layer is set to 10 nm or more. Preferably, the average thickness of the SiO2 layer is 20 nm or more.

[0031] On the other hand, by setting the average thickness of the SiO2 layer to 100 nm or less, it becomes possible to suppress the reaction with moisture as described above while ensuring the weldability of the surface-treated steel sheet 1 according to this embodiment. From this viewpoint, the average thickness of the SiO2 layer is set to 100 nm or less. Preferably, the average thickness of the SiO2 layer is 80 nm or less.

[0032] The average thickness of the SiO2 layer in the SiO2-coated Al flake 303 can be determined by observing the cross-section of the SiO2-coated Al flake 303 using a transmission electron microscope (TEM). More specifically, the SiO2-coated Al flake 303 in the surface treatment layer 30 is sampled by FIB processing or the like, and its cross-section is observed using TEM. Five SiO2-coated Al flakes are observed, and the thickness of the SiO2 layer is determined. The average of the five obtained values ​​is taken as the average thickness of the SiO2 layer.

[0033] Furthermore, in conventional manufacturing of power distribution boards and the like using alloyed hot-dip galvanized steel sheets, the alloyed hot-dip galvanized steel sheet is formed into the desired shape, and then the housing is welded using various welding methods such as laser welding and arc welding. In this process, the heat generated during welding can cause the Zn contained in the alloyed hot-dip galvanized layer to evaporate, resulting in a decrease in corrosion resistance. However, it has become clear that by including the SiO2-coated Al flakes 303 described above in the surface treatment layer 30, the evaporation of Zn from the plating layer during welding can be suppressed.

[0034] Al is an element that oxidizes more easily than Zn. By incorporating Al into the surface treatment layer 30, which is located on the surface side of the alloyed hot-dip galvanized layer 20, the Al contained in the surface treatment layer 30 melts faster than the Zn contained in the alloyed hot-dip galvanized layer 20 due to the heat input during welding. As a result, it is presumed that the evaporation of Zn is suppressed.

[0035] In the surface treatment layer 30 according to the present embodiment, it is important that Al is in a flaky form. FIG. 2 is an explanatory diagram for describing the SiO₂-coated Al flakes 303 in the surface treatment layer 30 according to the present embodiment. In the present embodiment, the Al contained in the surface treatment layer 30 is flaky Al. Note that in FIG. 2, the SiO₂ layer is not illustrated for convenience. The SiO₂-coated Al flakes 303 contained in the surface treatment layer 30 have an average particle size R (value including the SiO₂ layer) of 1.00 to 30.00 μm, and the ratio (R / t) of the average particle size to the average thickness t (value including the SiO₂ layer) is 10 or more.

[0036] Here, the average particle size R is determined by observing the surface of the target surface treatment layer 30 with a Scanning Electron Microscope (SEM), and when focusing on arbitrary Al, as shown in FIG. 2, the minor axis R of the target Al flake 303 S and the major axis R L are specified using the length measurement function attached to the scanning electron microscope or the like. The obtained minor axis R S and major axis R L are used to calculate the average value (0.5×(R S +R L )). Such measurement and calculation processing is performed on 20 arbitrary Al flakes. The average value of the 20 obtained values is defined as the average particle size R [unit: μm] of the SiO₂-coated Al flakes 303 in the target surface treatment layer 30.

[0037] In addition, the average thickness t is specified by observing a cross section in the thickness direction at an arbitrary position of the target surface treatment layer 30 using an SEM. The thickness of an arbitrary Al flake in the obtained cross section is specified using the length measurement function attached to the scanning electron microscope or the like. The thickness is similarly measured for 20 arbitrary Al flakes in the cross section, and the average value of the 20 obtained measurement values is defined as the average thickness t [unit: μm] of the SiO₂-coated Al flakes 303 in the target surface treatment layer 30.

[0038] Since Al flakes with an average particle size R of less than 1 μm are difficult to obtain, this increases the cost of manufacturing the surface-treated steel sheet according to this embodiment, which is undesirable. From this viewpoint, the average particle size R of the SiO2-coated Al flakes 303 according to this embodiment is set to 1.00 μm or more. Preferably, the average particle size R of the SiO2-coated Al flakes 303 is 5.00 μm or more, and more preferably 10.00 μm or more. By setting the average particle size R of the SiO2-coated Al flakes 303 to 1.00 μm or more, it becomes possible to more efficiently coat the surface of the alloyed hot-dip galvanized layer 20, and consequently, to achieve a higher gloss in the surface-treated steel sheet 1 according to this embodiment. Furthermore, when welding is performed on the surface-treated steel sheet 1 according to this embodiment, the Al oxide film can be formed more uniformly on the surface of the plating layer, and the evaporation of Zn during welding can be further suppressed.

[0039] On the other hand, if the average particle size R of the SiO2-coated Al flakes 303 exceeds 30.00 μm, there is a high possibility that the Al flakes will protrude from the surface treatment layer 30. When Al flakes protrude from the surface treatment layer 30, the protruding parts corrode, resulting in discoloration of the surface treatment layer 30 and a decrease in corrosion resistance. From this viewpoint, the average particle size R of the SiO2-coated Al flakes 303 according to this embodiment is set to 30.00 μm or less. By setting the average particle size R of the SiO2-coated Al flakes 303 to 30.00 μm or less, it becomes possible to prevent the protrusion of Al flakes as described above while more efficiently coating the surface of the alloyed hot-dip galvanized layer 20, and consequently, to achieve a higher gloss in the surface-treated steel sheet 1 according to this embodiment. Furthermore, when welding is performed on the surface-treated steel sheet 1 according to this embodiment, the Al oxide film can be formed more uniformly on the surface of the plating layer, and the evaporation of Zn during welding can be further suppressed. The average particle size R of the SiO2-coated Al flakes 303 is preferably 25.00 μm or less.

[0040] Because the surface treatment layer 30 according to this embodiment contains flake-shaped Al as described above, it is possible to reduce the amount of Al contained in the surface treatment layer 30 compared to the case where non-flake-shaped Al is contained, in order to achieve the Al flake coverage rate described in detail below. Furthermore, being able to reduce the Al content also means that the thickness of the surface treatment layer 30 can be reduced. From this viewpoint as well, the manufacturing cost when producing surface-treated steel sheets can be further reduced.

[0041] In addition, in the SiO2-coated Al flake 303 according to this embodiment, the minor axis R S and major axis R L The ratio (R L / R S ) is preferably 1.0 or more and 5.0 or less. Short axis R S and major axis R L The ratio (R L / R S The fact that the ratio is between 1.0 and 5.0 means that the shape of the SiO2-coated Al flake 303 when viewed from above is close to circular. By using such SiO2-coated Al flake 303, the SiO2-coated Al flake 303 with the above ratio can properly fill the depressions present on the surface of the alloyed hot-dip galvanized layer 20. This makes it possible to more efficiently coat the surface of the alloyed hot-dip galvanized layer 20 while suppressing the protrusion of the SiO2-coated Al flake 303 from the surface treatment layer 30. As a result, it becomes possible to achieve a higher coating rate with Al flakes, as detailed below, and consequently, a higher gloss level. S and major axis R L The ratio (R L / R S ) is more preferably 2.0 or less. S and major axis R L The ratio (R L / R S ) is the minor diameter R obtained when measuring the average particle size R in accordance with the above method. S and major axis R LIt can be calculated using these values.

[0042] Furthermore, in the SiO2-coated Al flake 303 according to this embodiment, the ratio of the average particle size to the average thickness t (R / t) is more preferably 50 or more. By having a ratio of the average particle size to the average thickness t (R / t) of 50 or more, the coating rate can be increased with a small amount of Al flakes, making it possible to efficiently improve gloss and corrosion resistance after welding.

[0043] On the other hand, in the SiO2-coated Al flake 303 according to this embodiment, the ratio of average particle size to average thickness t (R / t) is better the larger it is, and there is no particular upper limit. However, the ratio of average particle size to average thickness t (R / t) is practically limited to about 300.

[0044] In the surface treatment layer 30 according to this embodiment, the content of SiO2-coated Al flakes 303 is 0.15 to 12.00 g / m² in terms of metallic Al. 2 Preferably, the content of SiO2-coated Al flakes 303 is 0.15 g / m². 2 As a result, it becomes possible to reliably achieve the gloss improvement effect and the Zn evaporation suppression effect during welding described above. The content of SiO2-coated Al flake 303 is more preferably 1.00 g / m 2 The above is preferable, and more preferably 2.40 g / m 2 The above is true, and more preferably 5.00 g / m 2 That concludes the explanation. On the other hand, as explained earlier, the surface treatment layer 30 according to this embodiment contains SiO2-coated Al flakes 303 having the specific shape described above, so the content of SiO2-coated Al flakes 303 is 12.00 g / m 2 The following can be achieved: The content of SiO2-coated Al flakes 303 is more preferably 10.00 g / m². 2 The following, and more preferably 8.00 g / m² 2 The following applies:

[0045] To determine the content of SiO2-coated Al flakes 303 in the surface treatment layer 30 from the manufactured surface-treated steel sheet 1, the following procedure can be used. First, a sample is cut from the surface-treated steel sheet of interest. The obtained sample is then measured at 0.01 μm intervals from the surface toward the plating layer using a Glow Discharge Optical Emission Spectrometry (GD-OES) analyzer, and the average concentration of Al is determined. Here, using the same method as above, the area percentage of the region where Al is present is determined for multiple comparative samples with surface-treated layers of known Al flake content, and a calibration curve is prepared in advance based on its relationship with the pigment content. Using the calibration curve obtained in this way, it is possible to determine the Al flake content of the target sample.

[0046] In addition, in the surface treatment layer 30 according to this embodiment, the SiO2-coated Al flakes 303 may have a void shape (for example, a donut shape) as long as they have the external shape described above.

[0047] Furthermore, in the surface treatment layer 30 according to this embodiment, it is also possible to use, together with or in place of the SiO2-coated Al flakes 303, Al alloy flakes made from various Al alloys whose surfaces are coated with SiO2 (hereinafter also referred to as "SiO2-coated Al alloy flakes").

[0048] The average thickness of the SiO2 layer, the shape of the flakes, and the content of SiO2-coated Al alloy flakes in these SiO2-coated Al alloy flakes are the same as those of SiO2-coated Al flakes 303, so a detailed explanation is omitted below.

[0049] Examples of the SiO2-coated Al alloy flakes described above include SiO2-coated Al-Fe alloy flakes, SiO2-coated Al-Fe-Si alloy flakes, SiO2-coated Al-Mn alloy flakes, SiO2-coated Al-Mn-Si alloy flakes, SiO2-coated Al-Si alloy flakes, SiO2-coated Al-Si-Mg alloy flakes, SiO2-coated Al-Si-Cu alloy flakes, and SiO2-coated Al-Mg-Cu alloy flakes.

[0050] [Regarding other ingredients] The surface treatment layer 30 according to this embodiment may further contain, in addition to the above-described components, rust-preventive pigments, extender pigments, coloring pigments, rust inhibitors, dispersion stabilizers, etc., to the extent that the effects described above are not impaired. Furthermore, the surface treatment layer 30 according to this embodiment may contain, in addition to the above-described components, various chemical conversion treatment components such as chromate-based chemical conversion treatment components and non-chromate-based chemical conversion treatment components.

[0051] [Regarding the distribution of SiO2-coated Al flakes] Next, with reference to Figure 3, the distribution state of SiO2-coated Al flakes 303 in the surface treatment layer 30 according to this embodiment will be described. Figure 3 is a schematic diagram illustrating the distribution state of SiO2-coated Al flakes in the surface treatment layer of the surface-treated steel sheet according to this embodiment.

[0052] In the surface treatment layer 30 according to this embodiment, by using the SiO2-coated Al flakes 303 described above and going through the manufacturing method detailed below, the SiO2-coated Al flakes 303 are not uniformly dispersed in the thickness direction of the surface treatment layer 30, but rather become unevenly distributed in the region near the interface between the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30.

[0053] The following describes the uneven distribution of SiO2-coated Al flakes 303, focusing on its relationship with the average thickness of the surface treatment layer 30 (thickness d in Figure 3).

[0054] Here, as schematically shown in Figure 3, the surface of the alloyed hot-dip galvanized layer 20 has irregularities. The average thickness d of the surface treatment layer 30 is defined as the average thickness from the average position of the valleys of the irregularities to the surface of the surface treatment layer 30 at the interface between the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30, where such irregularities exist.

[0055] In the surface treatment layer 30 according to this embodiment, the SiO2-coated Al flakes 303 are unevenly distributed in the range from the interface between the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 to a position of average thickness d × (1 / 2) toward the surface of the surface treatment layer 30, as schematically shown in Figure 3. As shown in Figure 3, the uneven distribution of the SiO2-coated Al flakes 303 on the interface side with the alloyed hot-dip galvanized layer 20 makes it possible to suppress the diffuse reflection of light reflected at the interface with the alloyed hot-dip galvanized layer 20 by the SiO2-coated Al flakes 303. As a result, in the surface-treated steel sheet 1 according to this embodiment, the glossiness can be improved while keeping the SiO2-coated Al flake content low.

[0056] Furthermore, as described above, the uneven distribution of Al flakes allows Al to dissolve more quickly during welding, enabling a more uniform formation of an Al oxide film on the surface of the plating layer. This further suppresses the evaporation of Zn during welding.

[0057] More specifically, in the surface treatment layer 30 according to this embodiment, it is preferable that the amount of Al present in the SiO2-coated Al flakes 303, which are unevenly distributed near the interface with the alloyed hot-dip galvanized layer 20, up to a position of average thickness d × (1 / 2) is 70% or more.

[0058] Here, whether or not the SiO2-coated Al flakes 303 are unevenly distributed near the interface with the alloyed hot-dip galvanized layer 20 can be determined by observing the cross-sections obtained by cutting the surface treatment layer 30, the alloyed hot-dip galvanized layer 20, and the base steel sheet 10 in the thickness direction using a scanning electron microscope (SEM) equipped with an electron probe microanalyzer (EPMA). To obtain the cross-section to be observed, a metal such as gold can be coated onto the surface of the sample of the surface-treated steel sheet 1 of interest, then cut in the thickness direction, and the obtained cross-section can be polished using a known method.

[0059] Then, by obtaining backscattered electron (BSE) images of the cross-section of interest, as well as elemental mapping images for Al and Si elements, the distribution of Al flakes present up to an average thickness of d × (1 / 2) can be identified.

[0060] At this time, the value calculated by the following formula is taken as the proportion of Al present up to the position of average thickness d × (1 / 2). The percentage of Al present up to a point at an average thickness of d × (1 / 2) [%] = 100 × (Area of ​​Al flakes present up to the position of average thickness d × (1 / 2)) / (Area of ​​Al flakes present in the surface treatment layer)

[0061] The measurement and calculation process described above is performed for any five cross-sections, and the average of the percentages obtained in the five observation fields is treated as the percentage of Al present in the surface-treated steel sheet 1 up to a position of average thickness d × (1 / 2).

[0062] [Regarding coverage by SiO2-coated Al flakes] In the surface-treated steel sheet 1 according to this embodiment, the coverage rate R of the surface of the plated steel sheet (more specifically, the surface of the alloyed hot-dip galvanized layer 20) by the SiO2-coated Al flakes 303 as described above.C The coverage rate R of the SiO2-coated Al flake 303 is 20% or more. C This will be explained with reference to Figure 4. Figure 4 is a schematic diagram illustrating the coverage ratio of the surface-treated steel sheet 1 according to this embodiment. Note that in Figure 4, the irregularities present on the surface of the alloyed hot-dip galvanized layer 20 are not shown.

[0063] In considering the coverage rate by the SiO2-coated Al flakes 303, a scanning electron microscope (SEM) is used to observe the cross-sections obtained by cutting the surface treatment layer 30, the alloyed hot-dip galvanized layer 20, and the base steel sheet 10 in the thickness direction, as schematically shown in Figure 4. To obtain the cross-section to be observed, a metal such as gold is coated onto the surface of the sample of the surface-treated steel sheet 1 of interest, and then it is cut in the thickness direction, and the obtained cross-section is polished by a known method, as described above.

[0064] The obtained cross-section is observed using a SEM at a magnification of 1000x. At this time, the size of the observation field in the direction perpendicular to the thickness direction is denoted as L0, as shown in Figure 4. For example, the size of the observation field L0 can be 40 μm. Furthermore, for each SiO2-coated Al flake 303 present in the surface treatment layer 30, the width when projected perpendicularly to the plane in the direction perpendicular to the thickness direction is denoted as L. i This is expressed as follows: Here, the subscript i is a parameter representing the number of SiO2-coated Al flakes 303 within the field of view, and is an integer greater than or equal to 1. For each of the SiO2-coated Al flakes 303 present in the field of view, the width L when projected is... i The measurement is performed, and the sum of the obtained measurements is denoted as ΣLn (where n corresponds to the number of SiO2-coated Al flakes 303 present in the field of view).

[0065] In the example shown in Figure 4, there are four SiO2-coated Al flakes 303 in the surface treatment layer 30 within the field of view. In this case, as with SiO2-coated Al flakes 303A and 303B in Figure 4, when there is overlap of SiO2-coated Al flakes when viewed in the projection direction, the entire overlapping SiO2-coated Al flake is treated as a single unit, rather than adding up the projected lengths of the individual SiO2-coated Al flakes (not adding up the overlapping parts). In the example shown in Figure 4, SiO2-coated Al flakes 303A and 303B are treated as a single unit, and ΣLn is expressed as a value represented by L1 + L2 + L3.

[0066] Then, using L0 and ΣLn obtained as described above, the coverage R is calculated based on the following equation (101). C Calculate the percentage (in units of %). Coverage R C [%]=(ΣLn / L0)×100...Equation (101)

[0067] The above measurement and calculation process is performed for any five observation fields, and the coverage R obtained for the five observation fields is calculated. C The average value of this is treated as the coverage ratio R of the surface-treated steel sheet 1 of interest.

[0068] The above coverage ratio R C If the coverage ratio R is less than 20%, too much of the alloyed hot-dip galvanized layer 20 will not be covered by the SiO2-coated Al flakes 303, making it impossible to obtain the effect of improving gloss and suppressing the evaporation of Zn during welding. C When the coating ratio exceeds 20%, it becomes possible to obtain effects such as improved gloss and suppression of Zn evaporation during welding. C The coverage R of the SiO2-coated Al flakes 303 is preferably 50% or more, and more preferably 70% or more. C The higher the coverage R, the better. C It's fine if it's 100%.

[0069] Furthermore, the coverage ratio R can be controlled to a desired value by controlling the surface roughness of the alloyed hot-dip galvanized layer 20, the shape (average thickness of the SiO2 layer, average particle size R, average thickness t, etc.) and content of the SiO2-coated Al flakes 303 contained in the surface treatment layer 30, and the average thickness d of the surface treatment layer 30, as described later.

[0070] [Regarding average thickness] The average thickness of the surface treatment layer 30 according to this embodiment (thickness d in Figures 1 and 3) is preferably, for example, 1.0 to 10.0 μm. An average thickness of 1.0 μm or more of the surface treatment layer 30 ensures reliable improvement of corrosion resistance and gloss, as well as suppression of Zn evaporation during welding. More preferably, the average thickness of the surface treatment layer 30 is 2.0 μm or more, and even more preferably 4.0 μm or more. On the other hand, an average thickness of 10.0 μm or less of the surface treatment layer 30 ensures reliable improvement of corrosion resistance and gloss, as well as suppression of Zn evaporation during welding, while suppressing an increase in the manufacturing cost of the surface-treated steel sheet 1. More preferably, the average thickness of the surface treatment layer 30 is 9.0 μm or less, and even more preferably 7.0 μm or less.

[0071] The average thickness of the surface treatment layer 30 described above can be determined by observing the cross-section in the thickness direction at five arbitrary locations on the surface-treated steel sheet 1 of interest, measuring the thickness of the surface treatment layer 30 at each location, and then taking the average of the five obtained measurements.

[0072] The surface-treated steel sheet 1 according to this embodiment has been described in detail above with reference to Figures 1 to 4.

[0073] In the above explanation, the case in which the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 are provided on both surfaces of the base steel sheet 10 was given as an example. However, the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 only need to be provided on at least one surface of the base steel sheet 10. However, considering the overall corrosion resistance of the manufactured structural member, it is preferable that the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 are provided on both surfaces of the base steel sheet 10, as shown in Figure 1.

[0074] Furthermore, the surface-treated steel sheet 1 according to this embodiment may further have a chemical conversion coating layer (not shown) containing various known chemical conversion components, in addition to the alloyed hot-dip galvanized layer 20 and the surface treatment layer 30 described above.

[0075] (Regarding the manufacturing method of surface-treated steel sheets) Next, an example of a method for manufacturing a surface-treated steel sheet according to this embodiment will be described. The surface-treated steel sheet according to this embodiment is manufactured by first forming an alloyed hot-dip galvanized layer 20 on the surface of the base steel sheet 10 as described above, and then forming a surface treatment layer 30 on the surface of the alloyed hot-dip galvanized layer 20.

[0076] A hot-dip galvanizing method can be applied to form the alloyed hot-dip galvanized layer 20. In the manufacturing process of such plated steel sheets, first, the steel sheet to be used as the base material is rolled to the desired thickness using the Zenzimir method, then wound into a coil, and placed on the hot-dip galvanizing line.

[0077] In a hot-dip galvanizing line, the base steel sheet is continuously fed through a coil. At this time, the base steel sheet is heated and reduced at 800°C in an annealing facility installed on the line, for example, in an N2-5%H2 gas atmosphere with an oxygen concentration of 20 ppm or less. After that, it is air-cooled with N2 gas to approximately 20°C above the temperature of the subsequent plating bath, and then immersed in the plating bath.

[0078] Here, a molten plating metal having the chemical components necessary to achieve the desired plating layer is prepared in the plating bath. The temperature of the plating bath is set to be above the melting point of the plating metal (for example, around 460-660°C). When preparing the plating metal material, it is preferable to use pure metal (purity of 99% or higher) as the metallic material. First, a predetermined amount of the metallic material is mixed to achieve the above-described plating layer composition, and then completely melted using a high-frequency induction furnace or arc furnace under vacuum or inert gas displacement conditions. Furthermore, the plating metal mixed with the predetermined components is melted in the atmosphere, and the resulting molten material is used as the plating bath.

[0079] Furthermore, there are no particular restrictions on using pure metals when producing the plating metals described above; existing Zn alloys, Mg alloys, and Al alloys may be melted and used. In this case, there is no problem as long as an alloy with a predetermined composition and low impurity levels is used.

[0080] The base steel plate is immersed in the plating bath described above and then withdrawn at a predetermined speed. At this time, the amount of plating deposited is controlled, for example, by N2 wiping gas, so that the formed plating layer reaches the desired thickness. Here, conditions other than the bath temperature can be those of general plating operation, and no special equipment or conditions are required.

[0081] After removing the base steel sheet from the plating bath, an alloying heat treatment process (for example, a heat treatment process involving heating to a plate temperature of approximately 480-550°C), which is commonly performed in the production of alloyed hot-dip galvanized steel sheets, is carried out. This allows for the production of alloyed hot-dip galvanized steel sheets.

[0082] For example, a surface treatment layer 30 is formed on the surface of the alloyed hot-dip galvanized steel sheet manufactured as described above. In this case, a surface treatment agent is prepared by containing a base resin and SiO2-coated Al flakes, etc., in a desired concentration in various solvents (e.g., aqueous solvents such as pure water). In addition, treatment agents for forming other layers (e.g., chemical conversion coating layers, etc.) are prepared using various known methods as needed.

[0083] The product can be manufactured by applying various treatment agents, including the prepared surface treatment agent, to achieve the desired layer structure, and then drying and baking it.

[0084] Here, the application of various treatment agents can be carried out by generally known application methods, such as roll coating, curtain flow coating, air spraying, airless spraying, immersion, bar coating, and brush application.

[0085] Furthermore, during drying and baking, it is possible to control the distribution and coverage of Al flakes by controlling the baking temperature (the temperature reached on the metal surface), the residual heat content of the surface treatment agent (the so-called NV (Nonvolatile content) value), and the time interval from application of the surface treatment agent to baking.

[0086] For example, by setting the baking temperature within the range of 100 to 150°C, the surface gloss, Al flake distribution, and coverage can be made more desirable. Also, by setting the residual heat within the range of 5 to 25%, the surface gloss, Al flake distribution, and coverage can be made more desirable. Furthermore, by setting the time interval from application of the surface treatment agent to baking to 5 seconds or more, the surface gloss, Al flake distribution, and coverage can be made more desirable.

[0087] The above describes an example of a method for manufacturing a surface-treated steel sheet according to this embodiment. [Examples]

[0088] The surface-treated steel sheet according to the present invention will be described in detail below with reference to examples and comparative examples. Note that the following examples are merely examples of the surface-treated steel sheet according to the present invention, and the surface-treated steel sheet according to the present invention is not limited to the examples below.

[0089] (Preparation of base steel sheet and plating layer) In the verification example shown below, we prepared plated steel sheets (all manufactured by Nippon Steel Corporation) with four types of plating layers, as described below, formed on a 980MPa-class high-strength steel sheet with a thickness of 1.6 mm. GA: Alloyed hot-dip galvanized layer at 45 g / m² per side 2 A hot-dip galvanized steel sheet formed by the amount of adhesion GI: Hot-dip galvanized layer is 45 g / m² per side. 2 Hot-dip galvanized steel sheet formed by the amount of adhesion SD: Zn-11 mass%Al-3 mass%Mg-0.2 mass%Si alloy plating layer is 45 g / m² per side. 2 A Zn-based alloy plated steel sheet formed by the amount of adhesion ZM: Zn-6 mass%Al-3 mass%Mg alloy plating layer, 45g / m² per side 2 A Zn-based alloy plated steel sheet formed by the amount of adhesion

[0090] The surface roughness (Ra) of each prepared plated steel sheet was measured using a surface roughness meter (SURFCOM, manufactured by Tokyo Seimitsu Co., Ltd.) according to the method described above, and the results are shown in Table 1.

[0091] (Preparation of surface treatment agent for forming surface treatment layer) Polyurethane resin, polyester resin, and acrylic resin (all commercially available) were prepared as base resins. EMERAL® series manufactured by Toyo Aluminum Co., Ltd. was used as the SiO2-coated Al flake. The thickness of the SiO2 layer on the SiO2-coated Al flakes used is shown in Table 1 below. For comparison, general Al flakes without an SiO2 layer were also prepared.

[0092] The prepared base resin and Al flakes were mixed in pure water as a solvent in the concentrations shown in Table 1 below to create a surface treatment agent. Each of the resulting surface treatment agents was applied using a bar coater so that the average thickness of the surface treatment layer after drying was the value shown in Table 1 below. After baking in a hot air oven under the conditions shown in Table 1, it was air-cooled to room temperature. Multiple samples of surface-treated steel sheets were prepared for each level in this manner. In Table 1 below, the baking conditions are listed as heating residue (NV value) (%), the temperature reached on the metal surface (°C), and the time interval from application to baking (seconds).

[0093] After depositing Au onto the surface of each surface-treated steel sheet, the surface and cross-section were observed by SEM in accordance with the method described above to determine the major axis / minor axis ratio (R) of Al flakes in the surface treatment layer. L / R S ), average particle size R, average thickness t, coverage R C We measured the distribution of Al flakes and observed its distribution. The results are summarized in Table 1 below.

[0094] Furthermore, the distribution of Al flakes was scored as follows, based on the percentage values ​​calculated as described above. Grade A: Calculated percentage is 90% or higher B: The calculated percentage is between 70% and less than 90% C: The calculated percentage is less than 70%

[0095] [Table 1]

[0096] (evaluation) Two identical samples of the surface-treated steel plates were used as the upper and lower plates, and welded joints were fabricated by laser welding or arc welding. The gloss and color of the flat sections of the welded joints were then measured. Furthermore, the corrosion resistance and adhesion of the flat sections and welded sections of the welded joints were evaluated according to the following evaluation method. Details are as follows. The results are summarized in Table 2 below.

[0097] <Performance of laser welding / arc welding> For each surface-treated steel plate sample obtained, two identical samples were used as the upper and lower plates, and a welded joint was fabricated by overlapping fillet welding using laser welding or arc welding. Here, the size of the upper plate was 50 mm x 150 mm, the size of the lower plate was 30 mm x 150 mm, the overlap width of the upper and lower plates was 10 mm, and the gap between the plates was 0 mm.

[0098] The welding conditions for laser welding are as follows: Output: 3kW • Welding speed: 300 cm / min ·Forward / reverse advance angle: 0°

[0099] Furthermore, the welding conditions and welding wire used in the arc welding process are as follows: • Welding wire: Mild steel wire (YM-24T, φ1.2mm, manufactured by Nippon Steel Welding Industries Co., Ltd.) (C: 0.07 mass%, Si: 0.51 mass%, Mn: 1.2 mass%, P: 0.013 mass%, S: 0.004 mass%, Cu: 0.31 mass%) • Shielding gas: Ar + 20% CO2 • Welding torch tilt angle: 60° • Welding current: 140A • Welding voltage: 11.4V Welding speed: 80cm / min

[0100] <Glossiness> Glossiness was measured according to the method compliant with JIS Z8741 (1997). A commercially available digital angle-bending gloss meter (Suga Test Instruments Co., Ltd., model: UGV-6P) was used to measure the 60° specular gloss Gs(60°). In this measurement, the optical axis direction of the gloss meter was set to the L direction for each sample obtained. Separately, measurements were also taken when the optical axis direction of the gloss meter was set to the C direction, but no significant difference was observed compared to when the optical axis direction was set to the L direction. The evaluation was conducted according to the following criteria, and a score of A or higher was considered a passing grade. [Evaluation Criteria] Rating AAA: 60° mirror gloss exceeding 50 AA: 60° Mirror gloss level between 30 and 50 A: 60° Mirror gloss level is between 20 and 30 B: 60° Mirror gloss level of 20 or less

[0101] <color tone> Measurements were taken according to the method compliant with CIE 1976 as specified in JIS K5600-4-4 (1999). A commercially available colorimeter (Konica Minolta, Inc., CR-400Hand) was used. * The value was measured. Note that a * Value and b * The values ​​in all samples were within the range of -1.0 to +1.0. The evaluation was conducted according to the following criteria, and a score of A or higher was considered a passing grade. [Evaluation Criteria] Rating AA:L * Value over 80 A:L * The value is between 65 and 80. B:L * The value is 65 or less.

[0102] <Corrosion resistance evaluation> Each of the obtained welded joints was sealed at the end face and both ends of the weld bead, and then subjected to a combined cycle corrosion test in accordance with JASO M609-91. More specifically, one cycle consisted of salt spray (5% NaCl aqueous solution) at 35°C for 2 hours, drying (25% humidity) at 60°C for 4 hours, and wetting (95% humidity) at 50°C for 2 hours. After 60 cycles, the occurrence of red rust was evaluated as follows.

[0103] For the flat sections of welded joints, the percentage of red rust occurrence was calculated and evaluated according to the following evaluation criteria. A score of A or higher was considered acceptable. [Evaluation criteria: flat areas] Rating AAA: Red rust occurrence rate is 10% or less AA: Red rust occurrence area ratio is over 10% and 25% or less. A: Red rust occurrence area ratio is over 25% and 40% or less. B: Red rust occurrence rate exceeds 40%

[0104] For welded joints, the occurrence of red rust from the weld bead toe was evaluated according to the following evaluation criteria. A score of A or higher was considered acceptable. [Evaluation criteria: Welded joint] Rating AAA: Red rust width from the tip is 2.0 mm or less. AA: Red rust width from the tip is more than 2.0 mm and less than or equal to 4.0 mm. A: The width of the red rust from the tip is more than 4.0 mm but less than or equal to 5.0 mm. B: Red rust width from the toe is more than 5.0 mm

[0105] <Adhesion Evaluation> For each of the obtained welded joints, the end face and both ends of the weld bead were sealed, and then the joints were immersed in saltwater (3% NaCl aqueous solution, 50°C) for 500 hours. After that, adhesive tape (Nichiban CT405AP) was applied to the flat surface and the weld bead surface, and then peeled off. The area of ​​the coating attached to the tape was measured. The area ratio of the peeled coating to the total area of ​​the adhesive tape was calculated. [Evaluation criteria: flat areas] Rating AA: Paint film peeling area ratio is 20% or less A: Paint film peeling area ratio is more than 20% but less than or equal to 50% B: Paint peeling area ratio exceeds 50% [Evaluation criteria: Welded joint] Rating AA: Paint film peeling area ratio is 30% or less A: Paint film peeling area ratio is more than 30% but less than or equal to 60% B: Paint film peeling area ratio exceeds 60%

[0106] [Table 2]

[0107] As is clear from Table 2 above, welded joints using samples corresponding to the embodiments of the present invention exhibit excellent adhesion, as well as superior gloss and corrosion resistance, while welded joints using samples corresponding to the comparative examples of the present invention either do not exhibit excellent adhesion or fail to achieve both gloss and corrosion resistance. Although preferred embodiments of the present invention have been described in detail above with reference to the attached drawings, the present invention is not limited to these examples. It is clear to any person with ordinary skill in the art to which the present invention belongs that various modifications or alterations can be conceived within the scope of the technical idea described in the claims, and these are also understood to fall within the technical scope of the present invention.

[0108] The embodiments disclosed herein are illustrative and not restrictive in all respects. The embodiments described above may be omitted, replaced, or modified in various ways without departing from the appended claims, the technical scope of the invention as described later, and the spirit thereof. For example, the constituent elements of the embodiments described above can be combined in any way without impairing their effects. Furthermore, such any combination will naturally yield the effects and benefits of each constituent element in the combination, as well as other effects and benefits that will be obvious to those skilled in the art from the description herein.

[0109] Furthermore, the effects described herein are merely descriptive or illustrative, and not limiting. In other words, the technology according to the present invention may produce other effects that will be apparent to those skilled in the art from the description herein, in addition to or instead of the effects described above. [Explanation of Symbols]

[0110] 1. Surface-treated steel sheet 10 Base steel plate 20 Alloyed hot-dip galvanized layer 30 Surface treatment layer 301 Base resin 303 SiO2 coated Al flakes

Claims

1. A steel sheet having a base material steel sheet and an alloyed hot-dip galvanized layer on the steel sheet, The alloyed hot-dip galvanized layer has a surface treatment layer, The aforementioned surface treatment layer comprises a base resin and a surface that is SiO 2 SiO2 is an Al flake coated with a layer. 2 It contains coated Al flakes and The Al content in the surface treatment layer is 0.15 to 12.00 g / m². The average thickness of the aforementioned surface treatment layer is 1.0 to 10.0 μm. The SiO 2 The average thickness of the layer is 10 to 100 nm. The SiO 2 The average particle size R of the coated Al flakes is 1.00 to 30.00 μm, and the SiO 2 The ratio (R / t) of the average particle size to the average thickness t of the coated Al flakes is , 10 or more, The SiO 2 A surface-treated steel sheet in which the surface coverage rate of the alloyed hot-dip galvanized steel sheet with coated Al flakes is 20% or more. Here, the coverage ratio is the size of the observation field in the direction perpendicular to the thickness direction when the cross-section obtained by cutting the surface treatment layer, the alloyed hot-dip galvanized layer, and the steel plate is observed with a scanning electron microscope. 0 This is written as, and the SiO present in the observation field 2 When the length of the coated Al flake is denoted as ΣLn, it is the value given by the following equation (1). Coverage rate [%] = (ΣLn / L 0 ) × 100 ... Formula (1)

2. The surface-treated steel sheet according to claim 1, wherein the surface roughness of the alloyed hot-dip galvanized layer is 1.0 to 10.0 μm.

3. The SiO 2 The surface-treated steel sheet according to claim 1 or 2, wherein the average particle size R of the coated Al flakes is 10.00 to 30.00 μm.

4. The SiO 2 The coated Al flakes are made of the SiO 2 When viewed from above in the thickness direction of the coated Al flake, SiO 2 The minor axis of the coated Al flake is R S , the major axis is R L When written as such, the ratio (R L / R S The surface-treated steel sheet according to claim 1 or 2, wherein the coefficient of the surface treatment is 1.0 to 5.

0.

5. The surface-treated steel sheet according to claim 1 or 2, wherein the coverage rate is 50% or more.

Citation Information

Patent Citations

  • Production of aluminum pigment

    JP1993117722A

  • Surface treated metallic plate having metallic tone appearance

    JP2000325873A

  • Metallic effect pigment coated with SiO2, method for producing the metallic effect pigment, and use

    JP2013518948A

  • Chemically-treated steel sheet, manufacturing method for the same and chemical treatment liquid

    JP2016121390A

  • Coated steel sheet

    JP2018176632A